Reflexiones sobre el Trabajo Social hoy (2007)
ABSTRACT: This article contains elements of reflection and analysis around the debate on the configuration of the Social Work from representative authors in four countries: Spain, Argentina, Brazil and Chile. Tendencies are located that put in scene a specific social field in a permanent feedback around the goals and intentions in their processes of intervention and consider challenges for a Social Work that need reflections constructed collectively and based on the configuration of academic community, in order to not to fall in the proper relativism of the professions that limit his social action to the frame of the operative thing.